MANAJEMEN KINERJA ORGANISASI DINAS KOPERASI DAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) KOTA PEKANBARU - Sutinah, Aay; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Department of Cooperatives and Micro, Small and Medium Enterprises (SMEs) in Pekanbaru City is an implementation services unit in the field of Cooperatives and SMEs in Pekanbaru. One of the problems that occur are many SMEs and the informal sectors are not bankable yet due to the lack of managerial and financial capabilities. Then the lack of technology knowledge, marketing skills and the limitation of small enterprises to fulfill the products / services according to market demand, as well as limitations and lack of human resources. And the lack of protection for ideas and products produced by SMEs and the informal sectors as well as government policy or supporting regulations which they do not optimally support the development of SMEs. The current number of SMEs in Pekanbaru City around 15.291.000 spread over 12 districts in Pekanbaru. Supposedly with the large number of SMEs in Pekanbaru, SMEs can develop properly, the Departement provides special training for SMEs entrepreneur, as well as the good performance management of Department of Cooperatives and SMEs in Pekanbaru City to SMEs entrepreneur for the advancement of SMEs in Pekanbaru so that SMEs products can be known widely. But in fact, the products of SMEs have not been able to compete widely. Based on this, the author wanted to conduct a qualitative descriptive study on Organizational Performance Management of Department of Cooperatives and Micro, Small and Medium Enterprises (SMEs) in Pekanbaru City and the factors that influence it.Theoretical concept used by the author is the theoretical performance of Agus Dwiyanto: Productivity, Quality, Service, Responsiveness, Responsibility, Accountability. And factors that affecting organizational performance management. This study used a qualitative research with descriptive assessment. The collecting data of this study are by interview, observation and documentation.The results of this study indicate that the Organizational Performance Management of Department of Cooperatives and Micro, Small and Medium Enterprises (SMEs) in Pekanbaru City is not optimal yet. Then there are factors that affect the performance management encountered in the field two factors that affecting performance management are internal and external factor. The internal factor are quantity and quality of human resources, employee’s motivation. While external factors are the society and SMEs products.Keywords: Management, Performance, Organization, and Micro, Small and Medium Enterprises (SMEs)